Insect infection and immunity evolution, ecology, and mechanisms - Rolff, J. (Jens); Reynolds, Stuart Edward (Oxford : Oxford University Press, 2009)
The study of insect immune systems has accelerated rapidly in recent years & is now becoming an important interdisciplinary field. This book provides a coherent synthesis & is clearly structured around three broadly themed sections: mechanisms, interactions, & evolutionary ecology.
This book is published on the occasion of the Royal Entomological Society's Symposium on Insect infection and immunity in Sheffield, July 15-17 2009.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Insects -- Immunology -- Congresses; Insects -- Infections -- Congresses